The role of oxytocin in regulating loneliness in old age. (November 2021) - Abu Elheja, R.; Palgi, Y.; Feldman, R.; Zagoory-Sharon, O.; Keisari, S.; Shamay-Tsoory, S.G.
Abstract: Loneliness is prevalent in old age and is associated with reduced positive social interactions. Building on studies showing that oxytocin (OT) levels rise during social interactions, we hypothesized that following participation in positive social interaction involving synchronized movements, OT levels would increase, while state loneliness levels would diminish. A total of 63 older adults (aged M = 78.93, SD = 9.99; Range = 65–101) participated in the study. Participants completed emotional and social loneliness scales and provided saliva samples pre- and post-participation in the "mirror game", which requires movement synchronization and is known to promote connectedness and closeness. Results indicate a reduced state of loneliness following the mirror game. Importantly, the change in OT levels predicted the change in social loneliness, defined as the absence of social interactions with people in the social network. On the other hand, emotional loneliness, marked by deficient emotional contact, only decreased among participants who experienced high levels of closeness with their partner in the mirror game. Findings suggest that context-dependent change in endogenous OT may serve as biomarker for the social effects of oxytocin on loneliness in old age and can help in the development of targeted interventions for treating loneliness in old age. Highlights: Change in endogenous oxytocin in older adults had differential effects on the social and emotional dimensions of loneliness. Emotional loneliness decreased only at high levels of closeness with a partner following a social interaction. Context-dependent change in Oxytocin may serve as a potential mechanism underlying loneliness in old age.